Pengaruh Brand Image, Kualitas Pelayanan, dan Harga Terhadap Keputusan Konsumen dalam Menggunakan Jasa J&T Express - Meliani, Dwi (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This paper discusses the influence of brand image, service quality and price on consumer decisions in using JT Express delivery services. This research aims to understand the factors that influence consumer decisions in using JT Express delivery services, with a focus on the influence of brand image, service quality and price. The research results show that brand image, service quality and price are crucial factors in determining consumers' decisions to choose JT Express delivery services. Indonesian consumers prefer to use JT Express via applications and websites because of the ease of use and quality of service. In an era of globalization full of business competition, delivery service companies such as JT Express have become an important component of the global supply chain. Therefore, this research provides an in-depth understanding of the complexity of the interaction between brand image, service quality and price in influencing consumer decisions in using JT Express delivery services. Through this research, it is hoped that strategies can be implemented by delivery service companies to increase their attractiveness in a competitive market.